Evidence-based preventive care guidelines in pediatric primary care - Alzanbagi, Salah Mohammed; Ismael, Mohammed Zuhair; Alshehri, Hassan Saud; Almalki, Ohood Mohammed; Julaidan, Banan Mohammed; Miralam, Raed Talat; Eshan, Adeel Ibrahim; Khalifah, Reem Malak; Dawshi, Tahani Abdullah; Hawsawi, Ashraf Omar; Aljohani, Mohammed Saud; Babonji, Mohammed; et al. (International Journal Of Community Medicine And Public Health, 2025)
Evidence-based preventive care guidelines offer a systematic approach to early detection, prompt intervention, and the promotion of health, encompassing various aspects of physical, mental, and developmental well-being. Recently, more focus has been placed on improving guidelines for preventive interventions for pediatric populations. Primary care is considered a great venue for implementing these preventive interventions. In addition, primary care is the preferable place for parents to do such preventive interventions. Multiple authorized organizations have developed new guidelines and recommendations in order to improve the delivery of preventive measures in pediatric primary care in recent years. Unlike adults’ guidelines, pediatric preventive guidelines are confusing and of low quality, leading to more challenges faced by primary care providers. This review aimed to evaluate the quality of recent studies on this topic, with a focus on the accuracy and efficacy of current evidence-based guidelines. Despite advancements, challenges such as childhood obesity, speech disorders, and depression require further refinement of evidence-based guidelines, supported by high-quality research. Additionally, the integration of technology has demonstrated potential for enhancing the delivery and outcomes of pediatric primary care.